Hydrologic functioning of the deep critical zone and contributions to streamflow in a high‐elevation catchment: Testing of multiple conceptual models. Issue 4 (18th January 2019) - Dwivedi, Ravindra; Meixner, Thomas; McIntosh, Jennifer C.; Ferré, P.A. Ty; Eastoe, Christopher J.; Niu, Guo‐Yue; Minor, Rebecca L.; Barron‐Gafford, Greg A.; Chorover, Jon
Abstract: High‐elevation mountain catchments are often subject to large climatic and topographic gradients. Therefore, high‐density hydrogeochemical observations are needed to understand water sources to streamflow and the temporal and spatial behaviour of flow paths. These sources and flow paths vary seasonally, which dictates short‐term storage and the flux of water in the critical zone (CZ) and affect long‐term CZ evolution. This study utilizes multiyear observations of chemical compositions and water residence times from the Santa Catalina Mountains Critical Zone Observatory, Tucson, Arizona to develop and evaluate competing conceptual models of seasonal streamflow generation. These models were tested using endmember mixing analysis, baseflow recession analysis, and tritium model "ages" of various catchment water sources. A conceptual model involving four endmembers (precipitation, soil water, shallow, and deep groundwater) provided the best match to observations. On average, precipitation contributes 39–69% (55 ± 16%), soil water contributes 25–56% (41 ± 16%), shallow groundwater contributes 1–5% (3 ± 2%), and deep groundwater contributes ~0–3% (1 ± 1%) towards annual streamflow. The mixing space comprised two principal planes formed by (a) precipitation‐soil water‐deep groundwater (dry and summer monsoon season samples) and (b) precipitation‐soil water‐shallow groundwater (winter season samples). Groundwater contribution was most important during the wet winter season. During periods of high dynamic groundwater storage and increased hydrologic connectivity (i.e., spring snowmelt), stream water was more geochemically heterogeneous, that is, geochemical heterogeneity of stream water is storage‐dependent. Endmember mixing analysis and 3 H model age results indicate that only 1.4 ± 0.3% of the long‐term annual precipitation becomes deep CZ groundwater flux that influences long‐term deep CZ development through both intercatchment and intracatchment deep groundwater flows.